MEMBANGUN BUDAYA SEKOLAH YANG MENDUKUNG KARAKTER RELIGIUS, GOTONG ROYONG DAN DISIPLIN SOSIAL SISWA KELAS 5 DI SEKOLAH DASAR BRUDER DAHLIA PONTIANAK SELATAN - Marten, Marten; Aunurrahman, Aunurrahman; Hartoyo, Agung (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
One effective approach to character education is through the development of school culture. This study aims to describe the forms of school culture and the strategies implemented to instill religious values, cooperation, and social discipline among fifth-grade students at SD Bruder Dahlia Pontianak Selatan. This qualitative research focuses on school culture supporting these character values. The subjects include a vice principal in charge of curriculum, a fifth-grade teacher, and fifth-grade students. Data were collected through in-depth interviews, participatory observation, and documentation studies. The results indicate that SD Bruder Dahlia Pontianak Selatan has successfully developed a school culture that promotes religious character, cooperation, and social discipline through activities such as prayers, religious holiday celebrations, faith-building programs, Clean Friday initiatives, classroom duties, Development Fasting Actions (APP), donation campaigns, 5S culture, and life skills development. Teachers and school administrators implement strategies to build this culture holistically, systematically, involving all stakeholders, and consistently in practice.